2011
DOI: 10.1186/1471-2148-11-77
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear versus mitochondrial DNA: evidence for hybridization in colobine monkeys

Abstract: BackgroundColobine monkeys constitute a diverse group of primates with major radiations in Africa and Asia. However, phylogenetic relationships among genera are under debate, and recent molecular studies with incomplete taxon-sampling revealed discordant gene trees. To solve the evolutionary history of colobine genera and to determine causes for possible gene tree incongruences, we combined presence/absence analysis of mobile elements with autosomal, X chromosomal, Y chromosomal and mitochondrial sequence data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
136
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(171 citation statements)
references
References 82 publications
22
136
1
8
Order By: Relevance
“…Interestingly, a recent phylogenetic analyses of 83 mobile elements from Roos et al [19] indicated a closer association of the Procolobus/Piliocolobus clade to Asian colobines than to Colobus, a relationship that was not rejected by nuclear sequence data in their study, leading them to propose African colobines paraphyly hypothesis ( Figure 3(e)). This finding thus challenged the traditional view of the monophyly of African colobines.…”
Section: Phylogeny Of African Colobinaementioning
confidence: 93%
See 4 more Smart Citations
“…Interestingly, a recent phylogenetic analyses of 83 mobile elements from Roos et al [19] indicated a closer association of the Procolobus/Piliocolobus clade to Asian colobines than to Colobus, a relationship that was not rejected by nuclear sequence data in their study, leading them to propose African colobines paraphyly hypothesis ( Figure 3(e)). This finding thus challenged the traditional view of the monophyly of African colobines.…”
Section: Phylogeny Of African Colobinaementioning
confidence: 93%
“…In earlier analyses of morphological and molecular data, all supported that the African colobine forms a monophyletic clade [1,12,19], grouping Piliocolobus, Procolobus, and Colobus together [17][18][19][24][25][26]29,30] (Figure 3). Interestingly, a recent phylogenetic analyses of 83 mobile elements from Roos et al [19] indicated a closer association of the Procolobus/Piliocolobus clade to Asian colobines than to Colobus, a relationship that was not rejected by nuclear sequence data in their study, leading them to propose African colobines paraphyly hypothesis ( Figure 3(e)).…”
Section: Phylogeny Of African Colobinaementioning
confidence: 99%
See 3 more Smart Citations